2015
DOI: 10.18632/oncotarget.5464
|View full text |Cite
|
Sign up to set email alerts
|

Identification of drugs as single agents or in combination to prevent carcinoma dissemination in a microfluidic 3D environment

Abstract: Experiments were performed in a modified microfluidic platform recapitulating part of the in vivo tumor microenvironment by co-culturing carcinoma cell aggregates embedded in a three-dimensional (3D) collagen scaffold with human umbilical vein endothelial cells (HUVECs). HUVECs were seeded in one channel of the device to initiate vessel-like structures in vitro prior to introducing the aggregates. The lung adenocarcinoma cell line A549 and the bladder carcinoma cell line T24 were tested. Dose-response assays o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(45 citation statements)
references
References 35 publications
0
45
0
Order By: Relevance
“…3 consisting of a central gel channel flanked by two fluidic channels was utilized. Similar microfluidic platforms have been used for investigating angiogenesis, 13,14 EMT, 15,16 cancer cell-macrophage interactions, 17 intravasation 18 and extravasation. 19,20 For the present work, GFPexpressing HUVECs were seeded into one of the fluidic channels to form a uniform monolayer mimicking a blood vessel wall (Fig.…”
Section: Pro-metastatic Capabilities Of Tamsmentioning
confidence: 99%
“…3 consisting of a central gel channel flanked by two fluidic channels was utilized. Similar microfluidic platforms have been used for investigating angiogenesis, 13,14 EMT, 15,16 cancer cell-macrophage interactions, 17 intravasation 18 and extravasation. 19,20 For the present work, GFPexpressing HUVECs were seeded into one of the fluidic channels to form a uniform monolayer mimicking a blood vessel wall (Fig.…”
Section: Pro-metastatic Capabilities Of Tamsmentioning
confidence: 99%
“…The SFKs consist of nine members including: Src, Lck, Hck, Fyn, Blk, Lyn, Fgr, Yes, and Yrk (Boggon and Eck, 2004), while the JAK family has four members: JAK1, JAK2, JAK3 and TYK2 (Babon et al, 2014). In addition to being implicated in the progression of different epithelial tumors, including ovarian (Abubaker et al, 2014;Colomiere et al, 2009;Yue et al, 2012), lung (Zhang et al, 2007) and breast (Hedvat et al, 2009;Silva, 2004), selected members of each family (particularly Src and JAK2) are also associated with the regulation of the mesenchymal phenotype in various in vitro models of EMT (Bai et al, 2015;Balanis et al, 2013;Chua et al, 2012;Colomiere et al, 2009;Jo et al, 2009;Liu et al, 2014;Lo et al, 2007;Maschler et al, 2010;Nagathihalli and Merchant, 2012;Nam et al, 2002;Switzer et al, 2012;Yadav et al, 2011). The JAK and SFK signaling pathways therefore represent potential therapeutic targets in the treatment and prevention of invasive disease.…”
Section: Epidermal Growth Factor (Egf)-induced Emt In Basal-like Mda-mentioning
confidence: 99%
“…Microfluidic platforms that enable the precise integration of various biophysical and biochemical factors that govern tumor-vasculature interactions have also been developed [129131]. In one such study, Bai et al co-cultured a highly invasive bladder carcinoma cell line as aggregates embedded in a collagen scaffold in close proximity to an endothelial cell-lined channel mimicking a blood vessel to screen a panel of therapeutics (and combinations thereof) that can inhibit EMT [131].…”
Section: Modeling the Complex Tumor Microenvironment In 3dmentioning
confidence: 99%
“…In one such study, Bai et al co-cultured a highly invasive bladder carcinoma cell line as aggregates embedded in a collagen scaffold in close proximity to an endothelial cell-lined channel mimicking a blood vessel to screen a panel of therapeutics (and combinations thereof) that can inhibit EMT [131]. Using the degree of tumor aggregate dispersion as a measure of drug efficacy, it was found that the presence of endothelial cells enhanced the drug resistance of the bladder carcinoma cells.…”
Section: Modeling the Complex Tumor Microenvironment In 3dmentioning
confidence: 99%